Power Usage Monitoring Simulator for Estimating Usage Tariffs and Carbon Emission Levels at STO Bogor Based on IoT - Kusumaningrum, Nurwijayanti; Syafdi, Rizky (Compiler, 2024)
In this modern era, the efficiency of electricity usage has become one of the main concerns in the efforts toward sustainable energy management. The limitations in monitoring electricity usage have become a challenge for technicians, resulting in inefficiencies in data collection and discrepancies between the actual power usage and manual recordings. This research aims to design and develop a prototype of an Internet of Things (IoT)-based electricity usage monitoring tool to monitor electricity consumption in real-time, provide usage cost estimates, and measure the emission levels generated by the devices being used. It also facilitates data recording, accelerates decision-making, and improves electricity management with high accuracy, with a margin of error of 0.8% for power calculations and 0.5% for total power calculations. This allows for accurate measurement of voltage, load, power, and total power. The data obtained is used to calculate electricity tariffs based on actual consumption, such as a subscription fee of IDR 127,134, a rate per kWh of IDR 528.76, and a tax of 4%, resulting in a total cost of IDR 132,768 for 0.366 kWh usage over 60 minutes. The use of electronic devices also increases carbon emissions, with a 69% increase in the first 10 minutes and 28% in 60 minutes, highlighting the importance of environmental awareness and wise electricity usage.